Assessment of landscape ecological risk for a cross-border basin: A case study of the Koshi River Basin, central Himalayas. (October 2020) - Wang, Beibei; Ding, Mingjun; Li, Shicheng; Liu, Linshan; Ai, Jiahui
Highlights: Landscape ecological risk (LER) of a cross-border basin was assessed for sustainability. Landscape management in the Koshi River Basin with its fragile ecosystems is a challenge. LER decreased for 1990–2000 and increased for 2000–2017. The LER of the border between China and Nepal was high and it increased for 2000–2017. As the slope increased, the LER increased dramatically. Abstract: Developing a reasonable landscape ecological risk (LER) assessment is crucial to establishing LER alert mechanisms and promoting ecological protection, environmental management and social development. The typical cross-border Koshi River Basin (KRB), which has a sensitive human-environment relationship, was the study area. Using the LER assessment model, we evaluated the LER of the KRB in 1990, 2000, 2010 and 2017 and analyzed its spatial-temporal evolution characteristics. Spatial autocorrelation analysis was conducted to assess the clustering characteristics of the LER. The results showed the following: (1) The LER in the KRB showed a decreasing trend for 1990–2000 and an increasing trend for 2000–2017. High LER areas were mainly located on the border between China and Nepal, where the LER increased from 1990 to 2017. (2) The Nepal part of the KRB had the highest LER, and the Indian part had the lowest LER. As the slope increased, the extremely ecologically deteriorated areas generally increased. (3) The LER displayed a clustering characteristic in the KRB. High–high regions were distributed in extremely high LER regions, and low–low regions were located in extremely low and low LER regions. High human influence intensity was responsible for the increase in LER. Our study is valuable to the development and ecological security management of cross-border basins.